Phytochemical profiling, antioxidant capacities and anthocyanin compositions of the pigmented rice (Oryza sativa) of north-east India - SAHEWALLA, SURBHI; DAS, PRIYANKA; HAZARIKA, DIBYA JYOTI; BORO, ROBIN CHANDRA (The Indian Journal of Agricultural Sciences, 2023)
The association between the consumption of pigmented rice (Oryza sativa L.) and the improvement of human health is generating a great deal of interest among the researchers. An experiment was conducted during 2020 and 2021 at Assam Agricultural University, Jorhat, Assam to study the phytochemical profiling, antioxidant capacities and anthocyanin compositions of the 14 pigmented rice genotypes. The results were compared with the well-known traditional pigmented rice variety from Manipur, Poreiton Chakhao. The total phenolic content, total flavonoid content and total anthocyanin content ranged from 37.101 to 493.611 mg gallic acid equivalent/100 g, 53.316 to 151.667 mg quercetin equivalent/100 g and 1.006 to 13.904 mg cyanidin-3-chloride equivalent/100 g in the studied rice genotypes. The amount of rice showing 50% DPPH free radical scavenging activity (IC 50 value) ranged from 6.610 to 29.376 mg. The HPLC analysis revealed presence of both cyanidin-3-glucoside and peonidin-3-glucoside in the black pigmented rice genotypes, viz. TTB Black Rice 7, Chakhao-1, Chakhao-2 and TTB Black Rice 11. However, in the red rice genotypes analysed (Balam and Nepali Chakuwa), these two anthocyanins were not detected.